경피적 위루관 삽입술의 임상 경과: 단일 기관에서의 관찰 연구 - 이지현; Jihyun Lee; 심기남; Ki-nam Shim; 이강훈; Kang Hoon Lee; 이고은; Ko Eun Lee; 장지영; Ji Young Chang; 태정현; Chung Hyun Tae; et al. (The Korean journal of gastroenterology, 2018)
목적: 경피적 위루관 삽입술은 장기적인 경관 영양을 위해 가장 널리 사용되는 방법이다. 본 연구는 경피적 위루관 삽입술을 시행받는 환자들의 임상적인 특징과 임상 경과에 대하여 밝히고자 하였다. 대상 및 방법: 이화여자대학교 의과대학 부속 목동병원에서 2002년 1월부터 2013년 12월까지 위루관 삽입술을 시행받은 환자들의 의무기록을 후향적으로 조사하여, 환자들의 성별, 연령, 의식 상태, 기저 질환, 위루관 삽입술 시행 방법, 위루관 교체 여부 및 교체 방법, 교체 시기를 조사하였다. 결과: 대상 환자는 총 137명으로 남자가 86명(62.8%), 여자가 51명(37.2%)이었으며, 평균 연령은 67.85±16.97세였다. 위루관 삽입술이 필요한 기저 질환으로는 뇌출혈 및 뇌졸중을 포함한 뇌혈관 질환이 66명(48.2%)으로 가장 많았고, 두경부암(20명, 14.6%)과 파킨슨병(10명, 7.3%)이 그 뒤를 이었다. 133명(97.1%)이 내시경적 위루관 삽입을 받았고, 4명(2.9%)이 투시촬영 유도 위루관 삽입술을 시행받았다. 추적 기간 동안 1번이라도 위루관을 교체받은 90명의 환자 가운데 내시경적 교체를 시행받은 환자는 71명(78.9%), 투시촬영 유도 위루관 삽입술로 교체를 시행받은 환자는 4명(4.4%), 수기로 교체를 받은 환자는 15명(16.7%)이었으며 평균 교체 간격은 9.83±6.19개월이었다. 대상 환자 중 119명(86.9%)에서 위루관 삽입과 관련된 급성 합병증이 나타나지 않았으며, 9명(6.6%)의 환자에서 발생한 삽입 부위 감염이 가장 흔하게 발생한 합병증이었다. 지연 합병증은 25명(16.1%)의 환자에서 나타났으며, 가장 흔하게 발생한 합병증은 저절로 위루관이 제거된 것으로 21명(15.3%)의 환자에서 나타났다. 결론: 본 연구에서 경피적 위루관 삽입술은 장기적인 경관 영양을 위해 안전하게 사용될 수 있는 방법으로, 저자들은 본 연구가 추후 경피적 위루관 삽입술을 시행받는 환자들의 관리에 대한 지침을 마련하는 데 도움이 될 것으로 기대한다. Backgrounds/Aims: Percutaneous endoscopic gastrostomy (PEG) is a widely used method for long-term tube feeding. This study aimed to investigate the clinical characteristics and outcomes of patients who utilized long-term feeding tube via PEG. Methods: The medical records of 137 patients who underwent PEG tube insertion at Ewha Womans University Mokdong Hospital between January 2002 and December 2013 were reviewed. Results: PEG was indicated most frequently for cerebrovascular accidents (66 patients, 48.2%), followed by head and neck cancer (20 patients, 14.6%), and Parkinson’s disease (10 patients, 7.3%). The tubes were endoscopically inserted in 133 patients (97.1%); 4 patients (2.9%) underwent radiologic intervention. The tubes of 90 patients (65.7%) were exchanged at least once during the follow-up period. At the first exchange, 71 patients (78.9%) had their tubes exchanged by endoscopy, 24 patients (16.7%) by manually, and 4 patients (4.4%) by radiologic intervention. Of the 61 patients (44.5%) who had their tubes exchanged twice, 44 patients (72.1%) changed their tubes by endoscopic exchange, 13 patients (21.3%) by manually, and 4 patients (4.4%) via radiologic intervention. The mean time interval between the initial insertion and the first exchange was 9.83±6.19 months, and that between the initial insertion and the second exchange was 10.7±6.25 months. Of all the 137 patients, acute complications at initial insertion occurred in only 18 patients (13.1%), with insertion site infection (9 patients, 6.6%) being the most common acute complication. Conclusions: PEG appears to be a safe procedure for providing long-term tube feeding. Our results may help to develop strategies for further management of subjects receiving feeding tubes via PEG. (Korean J Gastroenterol 2018;71:24-30)